Survival, safety, and prognostic factors for outcome with Regorafenib in patients with metastatic colorectal cancer refractory to standard therapies: results from a multicenter study (REBECCA) nested within a compassionate use program. Issue 1 (December 2016) - Adenis, Antoine; de la Fouchardiere, Christelle; Paule, Bernard; Burtin, Pascal; Tougeron, David; Wallet, Jennifer; Dourthe, Louis-Marie; Etienne, Pierre-Luc; Mineur, Laurent; Clisant, Stéphanie; Phelip, Jean-Marc; Kramar, Andrew; et al.
Abstract Background Randomized trials have shown a survival benefit for regorafenib over placebo in patients with metastatic colorectal cancer (mCRC) that progressed after standard therapies. We evaluated survival and safety outcomes in patients treated with regorafenib in a real-life setting. Methods REBECCA is a cohort study nested within a compassionate use program designed to evaluate survival, safety, and potential prognostic factors for outcome associated with regorafenib in patients with mCRC refractory to standard therapies. Treatment effects according to various patient and tumour characteristics were evaluated using univariate and multivariate Cox proportional hazards regression models. Results Of 1178 patients in the compassionate use program, 654 were in the full analysis set. Median follow-up was 16.5 months. Median survival was 5.6 months. The 12-month survival rate was 22 %. Survival was independently and unfavourably affected by the following variables: poor performance status, short time from initial diagnosis of metastases to the start of regorafenib, low initial regorafenib dose, >3 metastatic sites, presence of liver metastases, andKRAS mutations. We identified prognostic groups of patients with low, intermediate, and high risk of death, with a median survival of 9.2, 5.2, and 2.5 months, respectively. Five-hundred-twenty-four patients (80 %) experienced at least one regorafenib-related adverse event, most commonly, fatigue, hand-foot skin reaction, diarrhea, anorexia, arterial hypertension, and mucositis. Conclusion The safety and efficacy profile of regorafenib in REBECCA are similar to those in randomized trials. Our prognostic model identified subgroups of mCRC patients who derived a minimal and maximum benefit from regorafenib. Trial registration Clinicaltrials.govNCT02310477 .